New Technique for Controlling Bleeding in Laparoscopic Liver Resection - Masoni, Luigi; Landi, MD, Leandro; Maglio, MD, Riccardo (International Journal of Innovative Research in Medical Science, 2019)
Introduction: The liver is a vascular-rich solid organ. Safe and effective dissection of the vessels and liver parenchyma, and control of intraoperative bleeding are the main concerns when performing liver resection. Controlling bleeding during laparoscopic hepatectomy(LH) is technically demanding, but reportedly associated with less estimated blood loss (EBL) than open surgery. Several studies have confirmed that intraoperative blood loss and postoperative transfusion are predictors of postoperative morbidity and mortality in liver surgery. Various methods and instruments have been developed during hepatectomy. Case presentation: The present study aimed to describe and evaluate hemorrhage control techniques during left lateral partial segmentectomy with use of endoscopic clips. Conclusion: control of intraoperative bleeding it is the most important aspect in liver resection. we propose a new technique for controlling bleeding in restricted operating spaces.